2022
DOI: 10.1002/chem.202201928
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)‐Catalyzed Hydroarylation of in situ Generated 3,3,3‐Trifluoro‐1‐propyne by C−H Bond Activation: A Facile and Practical Access to β‐Trifluoromethylstyrenes

Abstract: In this study, a practical and straightforward synthesis of β-(E)-trifluoromethylstyrenes by ruthenium-catalyzed C-H bond activation was developed. The readily available and inexpensive 2bromo-3,3,3-trifluoropropene (BTP), a non-ozone depleting reagent, was used as a reservoir of 3,3,3-trifluoropropyne. With this approach, the monofunctionalization of a panel of heteroarenes was possible in a safe and scalable manner (23 examples, up to 87% yield). Mechanistic investigations and density functional theory (DFT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…We speculated that this process is not 1,3-dipolar cycloaddition of BTP with azide. Based upon experiments and the literature [ 81 , 82 , 83 , 84 ], a possible pathway was proposed as Scheme 3 . Firstly, BTP is converted to TFP by treatment with DBU as the base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that this process is not 1,3-dipolar cycloaddition of BTP with azide. Based upon experiments and the literature [ 81 , 82 , 83 , 84 ], a possible pathway was proposed as Scheme 3 . Firstly, BTP is converted to TFP by treatment with DBU as the base.…”
Section: Resultsmentioning
confidence: 99%
“…In contemplating possible methods to carry out these click reactions, we recognized that 2-bromo-3,3,3-trifluoropropylene (BTP) is a commercially available reagent [ 68 , 69 , 70 , 71 , 72 ], and that its [3+2]-cycloaddition reactions have been employed to produce CF 3 -substituted pyrazoles [ 73 , 74 , 75 , 76 ], -isoxazoles [ 77 ] and -pyrroles [ 78 ]. Particularly informative are the observations that BTP can be readily transformed to TFP by treatment with bases [ 79 , 80 , 81 , 82 , 83 ] like i -Pr 2 NLi and 1,8-diazabicyclo[5.4.0]undec-7-ene DBU, and that compared to gaseous TFP, BTP is an inflammable, storage-stable and easily handled liquid. Regrettably, it was inscrutably neglected to utilize BTP in click reactions to synthesize the 4-trifluoromethyl 1,2,3-triazoles.…”
Section: Introductionmentioning
confidence: 99%
“…Besset et al recently reported an important strategy for synthesizing this scaffolds by the in situ generation of 3,3,3-trifluro-1-propyne from inexpensive non-toxic 2-bromo-3,3,3-trifluropropene (BTP) and the Ru( ii )-catalyzed hydroarylation of this alkyne with the aryl species of our interest. 29 The reaction conditions were found to be optimum with 5 mol% [RuCl 2 ( p -cymene)] 2 as the catalyst, 2.0 equiv. t BuONa as the base and DMF as the solvent at 90 °C for 24 h with 3-methyl-2-phenyl pyridine as the model substrate.…”
Section: Ru-catalyzed Hydroarylation-classificationmentioning
confidence: 99%
“…[25][26][27] As such, the development of efficacious synthetic strategies for expedient assembly of sophisticated triuoromethyl alkenes, especially those that are not readily available by using the extant methods, has evoked enormous interest from multi-discipline. [27][28][29] In the context, the Witting-type olenation [30][31][32] and transition-metalcatalyzed cross-coupling reactions 26,27,[33][34][35] evolve to be the state of the art, despite the remaining issues such as strongly basic reaction conditions, volatile and expensive tri-uoromethyl reagents, and poor stereoselectivities. With our continuing interest in the uoroarylation of p systems, 15,21,36,37 we would like to report herein our latest advancement in this territory (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%